Interdisciplinary Use of Argumentation among Religious Education and Philosophy Teachers-in-Training - Hacıeminoğlu, Esme (Religions, 2022)
Using document analysis, religion and philosophy pre-service teachers’ reflections on argumentation and in-class argumentation practices, which were received online, during the Special Teaching Methods course were examined. These documents included reflections of pre-service teachers on argumentation and in-class argumentation practices. Findings emerged in three dimensions: (a) the benefits of the use of argumentation (awareness and motivation skills, teaching via argumentation-based instruction), (b) difficulties in using argumentation (learning environment and motivational factors), and (c) suggestions, in which themes and codes were created in light of such dimensions. The acquired dimension of the use of argumentation consists of the themes of awareness, motivation, skills, and teaching. With regards to suggestions that can be drawn from this document analysis, both religious education and philosophy pre-service teachers stated that preliminary preparations should be made to apply the argumentation technique to the teaching process. The results offer insight on the integration of this technique into teaching as an instructional tool. As an important epistemological exercise, argumentation can be attained as a skill set during formal school education which may facilitate the integration of knowledge.